The Effect of Learning Motivation and Academic Discipline on Student Achievement - Delfia Seriani; Tutik Winarsih (The Eastasouth Management and Business, 2026)
This study is motivated by the urgent need to improve the quality of vocational education, particularly in efforts to maximize student academic achievement through internal factors—namely, learning motivation and academic discipline—which still vary significantly within school environments. This research is conducted to analyze the effect of learning motivation and academic discipline on students’ academic achievement, assessed both individually and collectively. The method used is a quantitative approach with a causal-associative research design, involving the entire population of 90 students using a saturation sampling technique. Data collection was conducted through questionnaires, interviews, and documentation, and was subsequently analyzed using statistical techniques, including multiple linear regression analysis. The results indicate that learning motivation and academic discipline have a positive and significant influence on academic achievement, both individually and jointly. These findings confirm that enhancing students’ motivation and discipline plays a crucial role in fostering optimal academic achievement. Thus, strengthening these two aspects should be a primary focus in learning strategies. The implications of this study provide a foundation for schools and educators in designing more effective strategies to improve the quality of learning and students’ academic outcomes.